Hydrogenation catalyst for petroleum resin and preparation method thereof
Through the catalyst of Ni-Co alloy and Mo-W composite oxide, combined with SiO2-Al2O3 support and honeycomb ceramic matrix, the high sulfur adaptability and reactant diffusion problems of petroleum resin hydrogenation catalyst are solved, and efficient aromatic ring hydrogenation and sulfur impurities removal are achieved, improving the stability and reaction efficiency of the catalyst.
Patent Information
- Application Number
- CN202510738840.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2025-07-25
AI Technical Summary
The existing petroleum resin hydrogenation catalysts have poor adaptability to high-sulfur raw materials and insufficient sulfide adsorption sites, resulting in frequent regeneration of the device, and the diffusion of a single reactant in the support structure is limited, making it difficult to synchronously and efficiently carry out aromatic ring hydrogenation and desulfurization reactions, which increases energy consumption and operation complexity.
A Ni-Co alloy and Mo-W composite oxide are used as active components, combined with a composite support of SiO2-Al2O3 three-dimensional silicon-aluminum bond network structure, a catalyst is prepared by ultrasonic assisted impregnation method, and a porous structure and a nitrogen-doped carbon layer are constructed on the surface to form a hollow multi-shell layer structure to prevent the agglomeration of the active components and are loaded on the honeycomb ceramic matrix.
It realizes synchronous and efficient removal of aromatic ring hydrogenation and sulfur impurities, improves the stability and reaction efficiency of the catalyst, reduces energy consumption and maintains long-term stability, and is suitable for high-sulfur environments.
Smart Images

Figure CN120361914A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts for petroleum resins, and specifically to a hydrogenation catalyst for petroleum resins and a preparation method thereof. Background Art
[0002] Currently, supported metal catalysts are generally used for the hydrorefining of petroleum resins, with alumina or silica gel as the carrier, and transition metal active components such as nickel and cobalt are dispersed on the surface. These catalysts achieve aromatic ring hydrogenation by cracking hydrogen through metal sites, but the active components are easily poisoned and deactivated by sulfides, and metal particles are prone to agglomeration at high temperatures, resulting in a rapid decline in catalytic efficiency. To improve stability, some processes use presulfurization treatment or add a protective bed layer, but this increases the system complexity and operating costs.
[0003] Therefore, the prior art has the following disadvantages Firstly, traditional catalysts have poor adaptability to high-sulfur raw materials, insufficient sulfide adsorption sites, and a sulfur capacity generally lower than 200 ppm, resulting in frequent regeneration of the device; Secondly, the carrier structure is single, the diffusion of reactants is restricted, and it is difficult to synchronously and efficiently carry out aromatic ring hydrogenation and desulfurization reactions. Industrial devices often require multi-stage series connection, resulting in a significant increase in energy consumption and operating pressure. These problems seriously restrict the purity and production economy of petroleum resin products. Summary of the Invention
[0004] The purpose of the present invention is to provide a hydrogenation catalyst for petroleum resins and a preparation method thereof to solve the problems raised in the background art above and overcome the existing technical defects.
[0005] To solve the above technical problems, the technical solution adopted by the present invention is: a hydrogenation catalyst for petroleum resins, including a catalyst, and the catalyst contains a main active component expressed by the general formula M1-M2 / SiO2-Al2O3, where M1 is an alloy of Ni and Co, and the atomic ratio of Ni to Co is 4:1; M2 is a composite oxide of Mo and W, and the molar ratio of Mo to W is 3:1; and SiO2-Al2O3 is a composite carrier formed by hydrolysis and condensation of a silicate aluminum precursor to form a three-dimensional silicon-aluminum bond network structure.
[0006] A preparation method of a hydrogenation catalyst for petroleum resins includes Step S1: Hydrolyze tetraethyl orthosilicate and pseudoboehmite under acidic conditions to form a SiO2-Al2O3 sol; Step S2: Add a CTAB template agent to the sol, age, dry, and then calcine to obtain a porous carrier of the catalyst; Step S3: Load nitrate and ammonium molybdate onto the Ni-Co alloy precursor or Mo-W composite oxide precursor in sequence by ultrasonic-assisted impregnation method; Step S4: Use a nitrogen-hydrogen mixed atmosphere to heat and reduce in an environment with a 5% nitrogen ratio to prepare the catalyst.
[0007] As a further scheme of the present invention: ZrO2 is incorporated into the SiO2-Al2O3 composite support, and the ZrO2 is dispersed in the silicon-aluminum grid gaps in the form of a tetragonal crystal phase.
[0008] As a further scheme of the present invention: the specific surface area of the composite support is 350m 2 / g, and the pore size of the composite support shows a bimodal distribution.
[0009] As a further scheme of the present invention: it further includes a nitrogen-doped carbon layer, the nitrogen-doped carbon layer is coated on the surface of the catalyst, and the nitrogen-doped carbon layer selectively adsorbs the unsaturated bonds in the resin through π-π bond interaction.
[0010] As a further scheme of the present invention: it further includes an alkali metal promoter, the alkali metal promoter is one of K or Cs oxides, and the alkali metal promoter is distributed on the surface of the support in the form of isolated sites.
[0011] As a further scheme of the present invention: the particles of the catalyst have a hollow multi-shell structure, and the hollow multi-shell structure prevents the main body of the active component from excessive sintering through the confinement effect.
[0012] As a further scheme of the present invention: it further includes a honeycomb ceramic matrix for loading the catalyst, the pore density of the honeycomb ceramic matrix is 300-600 CPSi, and the SiO2-Al2O3 composite support is coated in the pores of the honeycomb ceramic matrix.
[0013] Compared with the prior art, the beneficial effects of the present invention include: 1. On the one hand, the catalyst of the present application uses porous ceramics as the support, and on the other hand, the micron-to-nanometer through-channels constructed inside can effectively accelerate the diffusion of reactants and improve the reaction effect of the hydrogenation catalyst; 2. The surface of the support of the present application anchors the nickel-cobalt alloy that can efficiently crack hydrogen and generate active hydrogen atoms and the molybdenum-tungsten composite oxide double active components that selectively adsorb aromatic rings and sulfide molecules, and the cracked hydrogen atoms can quickly migrate to the adsorption sites through the surface of the support, and can simultaneously achieve the hydrogenation saturation of aromatic rings and the deep removal of sulfur impurities, thereby effectively improving the working efficiency of the hydrogenation catalyst; 3. The structural design of the hydrogenation catalyst of the present application can inhibit the high-temperature agglomeration of the active components through the physical confinement effect. During the use of the catalyst, the surface protective layer can block the sulfur poisoning erosion, enabling the catalyst to maintain long-term stability in high-temperature and high-sulfur environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The disclosure of the present invention will be described with reference to the accompanying drawings. It should be understood that the drawings are only for illustrative purposes and are not intended to limit the scope of protection of the present invention. In the drawings, the same reference numerals are used to refer to the same components. Among them: Figure 1 Schematically shows a schematic flow chart of a method proposed according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0015] It is easy to understand that according to the technical solution of the present invention, without changing the essential spirit of the present invention, those of ordinary skill in the art can propose various replaceable structural forms and implementation manners. Therefore, the following detailed embodiments and the accompanying drawings are only exemplary descriptions of the technical solution of the present invention, and should not be regarded as the whole of the present invention or as a limitation or restriction on the technical solution of the present invention.
[0016] Please refer to Figure 1 , according to an embodiment of the present invention, a hydrogenation catalyst for petroleum resin is shown in combination with the accompanying drawings, including a catalyst. The catalyst contains an active component main body expressed by the general formula M1-M2 / SiO2-Al2O3. M1 is an alloy of Ni and Co, and the atomic ratio of Ni to Co is 4:1. That is, in chemical engineering, the process of preparing nickel tetracarbonyl Ni(CO)4 from Ni and 4Co under normal temperature and pressure. Among them, the Ni-Co alloy reduces the hydrogen adsorption energy through d-orbital electron sharing and can reduce the H2 dissociation energy to 0.58 eV. Specifically, both Ni and Co in this catalyst are transition metals, and the electron configuration of Ni is 3d 8 4s 2 , Co3d 7 4s 2 , so in the process of forming the Ni-Co alloy, the atoms of the two metals will be evenly distributed in the lattice and form a solid solution. And alloying causes the d-orbital electrons to hybridize and form new electron states, which are specifically manifested as 1. d-band center shift: It is found through density functional theory calculations that the d-band center of the Ni-Co alloy approaches the Fermi level compared with pure Ni or Co. This shift reduces the filling of the antibonding orbital between the metal surface and the H2 molecule, thereby weakening the H-H bond and promoting the dissociation of the catalyst. Moreover, Ni provides a high density of d-orbital electrons, promoting the initial adsorption ability of H2, and Co can effectively reduce the dissociation energy barrier of the metal through electron sharing with Ni.
[0017] 2. Charge redistribution: Part of the d-orbital electrons of Co are transferred to Ni, forming an electron-rich region of Ni and an electron-deficient region of Co, optimizing the surface charge distribution of the catalyst and enhancing the adsorption capacity for H2; Therefore, the hybrid d-orbitals on the alloy surface form an intermediate state, which can stabilize the transition state of H2 dissociation (partial breakage of the H-H bond), reducing the dissociation energy change from H2 to two H atoms from approximately 0.85 eV for pure Ni to 0.58 eV (DFT calculated value). This synergistic effect not only improves the hydrogenation activity of the catalyst but also optimizes the selectivity and stability of the catalyst, which is the core mechanism for its efficient application in the hydrogenation of petroleum resins.
[0018] Therefore, in this application, after generating the Ni-Co alloy by the impregnation reduction method, the structure of the Ni-Co alloy was characterized and analyzed. In this table, a control group (XRD, XPS, and TEM-EDS method groups) and an experimental group (H2-TPD) were divided to verify the data of the reduced dissociation energy of H2 and obtain the data in Table 1. Table 1. Control test table for the dissociation energy of H2 As can be seen from the above table, the dissociation energy of H2 was confirmed to be reduced through the exchange reaction of the experimental group of H2-TPD. After retrieval, in the content recorded in the literature "Journal of Catalysis, 2015, 331, 162 - 171", the dissociation energy for separating H2 in the pure Ni catalyst is 0.85 eV. In the content recorded in the literature "ACS Catalysis, 2018, 8, 11094 - 11103", the dissociation energy for separating H2 in the Ni-Fe alloy is 0.85 eV. In the content recorded in the literature "Applied Catalysis B: Environmental, 2019, 244, 536 - 544", the dissociation energy for separating H2 in the Ni-Pd alloy is 0.65 eV. Therefore, the dissociation energy for separating H2 in the Ni-Co alloy used in this application is 0.58 eV, which is the best performance in the existing technology.
[0019] In addition, M2 is a composite oxide of Mo and W, and the molar ratio of Mo to W is 3:1. The Mo-W composite oxide can inhibit the resin cracking side reaction by forming acid-metal synergistic sites of NH3-TPD. Therefore, the Mo-W composite oxide realizes the selective adsorption and directional hydrogenation of resin molecules by constructing weak acid-metal synergistic sites, while inhibiting the cracking side reaction caused by strong acids or electron overload. Specifically, the Mo-W composite oxide can construct weak acid centers with a proportion greater than 70%. After the synergistic effect of the weak acid centers and metal sites, the resin unsaturated bonds can be preferentially adsorbed and the hydrogenation intermediates can be stabilized, thereby inhibiting the cracking side reaction caused by strong acids.
[0020] In summary, under the action of the Ni-Co alloy optimizing the surface electronic structure through d-orbital electron sharing to reduce the H2 dissociation energy to 0.58 eV and significantly improving the hydrogen activation efficiency, the Mo-W composite oxide can reduce the formation of low-molecular by-products while achieving high-efficiency hydrogenation through a synergistic effect, realizing the highly selective deep hydrogenation of petroleum resin and achieving the balance between high hydrogenation efficiency and low by-products.
[0021] In addition, SiO2-Al2O3 is a composite support formed by the hydrolysis and condensation of a silicate-aluminate precursor to form a three-dimensional silicon-aluminum bond network structure. In this process, Si and Al form a three-dimensional cross-linked network through strong covalent Si-O-Al bonds. The bond energy of 452 kJ / mol contained in Si-O-Al is significantly higher than the bond energy of 444 kJ / mol contained in a single Si-O-Si bond and the bond energy of 318 kJ / mol contained in an Al-O-Al bond. Therefore, during the bonding process of the Si-O-Al bond, not only are the structural defects of the catalyst reduced, but also the local electron distribution of the catalyst is optimized through charge balance, forming a stable crystal framework possessed by the composite support (whose framework has an excellent stable structure similar to sodalite).
[0022] Other embodiments of the present invention: ZrO2 is incorporated into the SiO2-Al2O3 composite support. ZrO2 is dispersed in the silicon-aluminum grid gaps in the tetragonal crystal phase and ZrO2 accounts for 3% of the mass of the support. The introduction of ZrO2 is achieved by the characteristic of the tetragonal crystal phase ZrO2 having oxygen vacancy defects and using Lewis acid sites to promote the π-bond activation of aromatic rings in the resin, effectively enhancing the metal-support interaction strength and ensuring the efficient utilization of H2.
[0023] Other embodiments of the present invention: The specific surface area of the composite support is 350 m 2 / g. The pore size of the composite support shows a bimodal distribution. In this embodiment, the bimodal pore structure can achieve hierarchical mass transfer of the composite support and reduce the amount of coking, ensuring the activity retention rate during the continuous operation of the catalyst. At the same time, a nitrogen-doped carbon layer is coated on the surface of the catalyst. The nitrogen-doped carbon layer selectively adsorbs unsaturated bonds in the resin through π-π bond interaction, so that the resin backbone can be prevented from breaking by the directional π-π bond.
[0024] Other embodiments of the present invention: It also includes an alkali metal promoter. The alkali metal promoter is one of K or Cs oxides. The alkali metal promoter is distributed on the surface of the support in the form of isolated sites. In this embodiment, the alkali metal can inhibit the cracking reaction of the catalyst by neutralizing strong acid centers and ensure the use activity of the catalyst.
[0025] Other embodiments of the present invention: The catalyst particles have a hollow multi-shell structure. The hollow multi-shell structure prevents excessive sintering of the active component matrix through the confinement effect. The surface of the catalyst is modified with a chiral ligand, and the ligand is one of L-proline derivatives or tartrate complexes. The catalyst adopts a hollow multi-shell structure design that usually includes 3 to 5 layers of shells with a layer spacing of about 10 nanometers, which can effectively isolate the active components through the physical confinement effect and significantly inhibit atomic migration and sintering phenomena in a high-temperature environment. After the catalyst in this embodiment is maintained at 800 degrees Celsius for 10 hours, the specific surface area of the catalyst only decreases by 8%, successfully maintaining the high dispersion of the active sites; at the same time, the internal hierarchical pore structure has a coverage range of 30 nanometers, greatly optimizing the mass transfer efficiency of reactants and products, and increasing the catalytic turnover frequency to 2.7 times the original level.
[0026] In addition, the surface of the catalyst is further modified with L-proline derivatives or tartrate complex chiral ligands. XPS analysis shows that the proportion of nitrogen and oxygen atoms increases by 12%. These ligands cooperate through hydrogen bond networks and steric hindrance effects to precisely regulate the spatial orientation of substrate molecules, achieving an enantioselectivity of up to 98%. Specifically, the confinement microenvironment formed by the hollow structure not only promotes the local enrichment of reactants but also stabilizes the key reaction transition states, thereby enhancing the overall catalytic efficiency.
[0027] Other embodiments of the present invention: It further includes a honeycomb ceramic matrix for the catalyst to be loaded. The pore density of the honeycomb ceramic matrix is 300 - 600 CPSi. The SiO2 - Al2O3 composite support is coated in the pores of the honeycomb ceramic matrix. The catalyst constructs a three-dimensional through-support with the honeycomb ceramic as the matrix, and its pore density is controlled at 300 to 600 pore units per square inch. The inner walls of the pores are uniformly coated with the SiO2 - Al2O3 composite support to form an active site anchoring layer with a high specific surface area. The honeycomb structure optimizes the gas flow distribution through regularly arranged hexagonal pores, reducing the pressure drop by more than 40%. At the same time, the acidic sites of the composite support and the hollow multi-shell catalyst particles act synergistically to enable efficient diffusion and interfacial contact of reactants in the pores.
[0028] A preparation method of a hydrogenation catalyst for petroleum resin, including Step S1: Hydrolyze tetraethyl orthosilicate and pseudo-boehmite under acidic conditions to form a SiO2-Al2O3 sol. Specifically, mix tetraethyl orthosilicate and pseudo-boehmite at a molar ratio of 3:1, add a 0.5 mol / L nitric acid solution to adjust the pH of the system to 2-3, and magnetically stir in a 60°C constant temperature water bath for 3 hours. During the hydrolysis process, the Si-O-C2H5 bonds of tetraethyl orthosilicate break under acidic conditions to generate Si-OH active sites, which form a three-dimensional network structure of SiO2-Al2O3 sol through co-condensation with the Al(OH)3 colloid released by pseudo-boehmite. After the sol is passed through a 0.22 μm filter membrane to remove unhydrolyzed particles, it is left to stand and age for 12 hours to improve the colloidal homogeneity; Step S2: Add a CTAB template agent to the sol, age, dry, and then calcine to obtain a porous support for the catalyst. Specifically, gradually add a CTAB template agent with a concentration of 0.2 mol / L to the sol. The mass ratio of CTAB to SiO2 in the sol is 1:15. The resulting mixture is transferred to a polytetrafluoroethylene high-pressure reactor. After the reaction, it is placed in a tube furnace and heated to 550°C at a rate of 2°C / min and calcined in an air atmosphere for 4 hours. After removing the template agent, a SiO2-Al2O3 porous support with a pore size distribution of 3-10 nm and a specific surface area of 380 m² / g is obtained; Step S3: Use ultrasonic-assisted impregnation to sequentially load 3.4 mol / L nitrate and 5.8 mol / L ammonium molybdate onto a 0.6 g Ni-Co alloy precursor or Mo-W composite oxide precursor. When impregnating the Mo-W composite oxide precursor, citric acid is added as a complexing agent, and the molar ratio of the complexing agent to the Mo-W composite oxide precursor is 1:1. Specifically, first impregnate the porous support in a mixed solution of nickel nitrate and cobalt nitrate and ultrasonically treat for 30 minutes to promote diffusion in the pores. Then add citric acid with a molar ratio of 1:1 to the total metal molar amount as a complexing agent and stir at 60°C to form a transparent chelating solution; then load the above solution onto the support surface by the equal-volume impregnation method and calcine for 3 hours under nitrogen protection to generate a highly dispersed MoO3-WO3 composite oxide; Step S4: Use a nitrogen-hydrogen mixed atmosphere to heat and reduce to prepare the catalyst in an environment with a 5% nitrogen content. Specifically, place the catalyst precursor loaded with the precursor in a fixed-bed reactor, introduce a nitrogen-hydrogen mixed gas containing 5% nitrogen, and heat to 450°C at a rate of 5°C / min, and carry out constant-temperature reduction for 4 hours.
[0029] Finally, a catalyst with a SiO2-Al2O3 support as the core and bifunctional active sites of Ni-Co alloy and Mo-W oxide uniformly distributed on the surface can be prepared. Its metal dispersion degree reaches 85%, and the BET specific surface area remains 320 m² / g, which is suitable for the aromatic ring hydrogenation in petroleum resins and the deep removal of sulfur-containing impurities.
[0030] Working principle: On the one hand, the catalyst uses porous ceramics as the carrier. On the other hand, the micron-to-nanometer through-channels constructed inside can effectively accelerate the diffusion of reactants and improve the reaction effect of the hydrogenation catalyst; At the same time, two active components, namely nickel-cobalt alloy that can efficiently crack hydrogen to generate active hydrogen atoms and molybdenum-tungsten composite oxide that selectively adsorbs aromatic rings and sulfide molecules, are anchored on the surface of the carrier. Moreover, the cracked hydrogen atoms can quickly migrate to the adsorption sites through the surface of the carrier, and the aromatic ring hydrogenation saturation and deep sulfur impurity removal can be achieved synchronously, thus effectively improving the working efficiency of the hydrogenation catalyst; In addition, the structural design of the hydrogenation catalyst can inhibit the high-temperature agglomeration of active components through the physical confinement effect. When the catalyst is used, the surface protective layer can block sulfur poisoning erosion, enabling the catalyst to maintain long-term stability in high-temperature and high-sulfur environments.
[0031] The technical scope of the present invention is not limited to the content described above. Those skilled in the art can make various deformations and modifications to the above embodiments without departing from the technical idea of the present invention, and these deformations and modifications should all fall within the protection scope of the present invention.
Claims
1. A hydrogenation catalyst for petroleum resin, characterized in that, It includes a catalyst, and the catalyst contains a main active component expressed by the general formula M1-M2 / SiO2-Al2O3, where M1 is an alloy of Ni and Co, and the atomic ratio of Ni to Co is 4:1; M2 is a composite oxide of Mo and W, and the molar ratio of Mo to W is 3:1; and SiO2-Al2O3 is a composite support formed by hydrolysis and condensation of a aluminosilicate precursor to form a three-dimensional silicon-aluminum bond network structure.
2. The hydrogenation catalyst for petroleum resin according to claim 1, characterized in that, ZrO2 is incorporated into the SiO2-Al2O3 composite support, and the ZrO2 is dispersed in the silicon-aluminum grid gaps in the tetragonal crystal phase.
3. The hydrogenation catalyst for petroleum resin according to claim 2, wherein, The specific surface area of the composite support is 350 m 2 / g, and the pore size of the composite support presents a bimodal distribution.
4. The hydrogenation catalyst for petroleum resin according to claim 3, wherein It also includes a nitrogen-doped carbon layer, the nitrogen-doped carbon layer coats the surface of the catalyst, and the nitrogen-doped carbon layer selectively adsorbs the unsaturated bonds in the resin through π-π bond interaction.
5. The hydrogenation catalyst for petroleum resin according to claim 4, characterized in that, It also includes an alkali metal promoter, the alkali metal promoter is one of K or Cs oxides, and the alkali metal promoter is distributed on the surface of the support in the form of isolated sites.
6. The hydrogenation catalyst for petroleum resin according to claim 5, characterized in that, The particles of the catalyst have a hollow multi-shell structure, and the hollow multi-shell structure prevents the excessive sintering of the main active component through the confinement effect.
7. The hydrogenation catalyst for petroleum resin according to claim 6, wherein It also includes a honeycomb ceramic matrix for loading the catalyst, the pore density of the honeycomb ceramic matrix is 300-600 CPSi, and the SiO2-Al2O3 composite support is coated in the pores of the honeycomb ceramic matrix.
8. A preparation method of a hydrogenation catalyst for petroleum resin according to claim 7, characterized in that, Includes Step S1: Hydrolyze tetraethyl orthosilicate and pseudo-boehmite under acidic conditions to form a SiO2-Al2O3 sol; Step S2: Add a CTAB template agent to the sol, age, dry, and then calcine to obtain a porous support of the catalyst; Step S3: Use the ultrasonic-assisted impregnation method to load nitrate and ammonium molybdate onto the Ni-Co alloy precursor or the Mo-W composite oxide precursor in sequence; Step S4: Use a nitrogen-hydrogen mixed atmosphere to heat and reduce in an environment with a 5% nitrogen content to prepare the catalyst.
Citation Information
Cited By
Catalyst for regenerating waste mineral oil as well as preparation method and application of catalyst
CN121266633A